Moda w zakresie morfologii współczesnych emporionimów - Rutkiewicz-Hanczewska, Małgorzata (Poznańskie Spotkania Językoznawcze, 2014)
The paper deals with news linguistic tendencies in the creation of modern names of retail and service. It is described not only transonymisation, onymisation, but also morphological constituents of modern names of retail and service. Units created by suffixes and references to another names are considered as a fashionable. The first are neologisms and one creates them by means of morphemes -nia (-ownia) oraz -arnia, -ernia, -eria, -teka. The latter are created for free form using of proper or common name that they allow for finding their initial structure (Szmatrix < Matrix).